Studi Komparasi Minat Membaca Anak antara Buku Cetak dan Buku Elektronik pada Siswa Kelas 5 SDN Pondok Ranji IV - Lia Permatasari; Mas Roro Diah Wahyu Lestari (Journal of Academia Perspectives, 2023)
Reading books is considered as an important activity that supports literacy development. The low interest in reading students cannot be separated from the culture of reading that is created in the family and school environment. The purpose of this study was to determine differences in students’ reading interest between printed books and electronic books in grade 5 of Pondok Ranji IV SDN, Ciputat District, South Tangerang City. This research is a comparative causal study (Ex Post Facto) with a quantitative approach. The population in this study were students at SDN Pondok Ranji IV with a sample of 30 respondents. Data collection techniques in this study used questionnaires and tests. Data were processed and analyzed quantitatively using SPSS 25.0. The data analysis method used in this study is multiple linear regression. The findings of this study indicate that interest in reading printed books has no significant effect on students’ interest in reading. Meanwhile, interest in reading electronic books has a significant effect on students’ interest in reading. Therefore, educators can consider using electronic book media as a learning resource for students. Based on the results of the regression analysis, the variable interest in reading printed books (X1) and the variable interest in reading electronic books (X2) on students’ reading interest has a value of a = constant 3.121. So, it can be concluded that there are differences in the level of reading interest of students who use printed books and electronic books.